Serum NfL (Neurofilament Light Chain) Levels and Incident Stroke in Adults With Diabetes Mellitus. Issue 7 (July 2019) - Korley, Frederick K.; Goldstick, Jason; Mastali, Mitra; Van Eyk, Jennifer E.; Barsan, William; Meurer, William J.; Sussman, Jeremy; Falk, Hayley; Levine, Deborah
Abstract : Background and Purpose—: Effective stroke prevention depends on accurate stroke risk prediction. We determined the discriminative ability of NfL (neurofilament light chain) levels for distinguishing between adults with diabetes mellitus who develop incident stroke and those who remain stroke free during a 7-year follow-up period. Methods—: We performed a case-control study of participants selected from the previously completed ACCORD trial (Action to Control Cardiovascular Risk in Diabetes). Cases were all ACCORD subjects who were stroke free at enrollment and developed incident stroke during follow-up (n=113). Control subjects (n=250) were randomly selected ACCORD subjects who had no stroke events either before or after randomization. NfL was measured in baseline samples using Single Molecule Array technology (Quanterix). Results—: Baseline NfL levels were higher in stroke subjects, compared to controls, after adjusting for age, race, blood pressure, weight, and the Framingham Stroke Risk Score. Relative to the subjects in the lowest quintile of NfL levels, the hazard ratios of incident stroke for subjects in the second to fifth quintiles were 3.91 (1.45–10.53), 4.05 (1.52–10.79), 5.63 (2.16–14.66), and 9.75 (3.84–27.71), respectively, after adjusting for race and Framingham Stroke Risk Score. Incorporating NfL levels into a predictive score that already included race and Framingham Stroke Risk Score increased the score's C statistic from 0.71 (95% CI, 0.66–0.77) to 0.78 (95% CI, 0.73–0.83), P <0.001. Older age, nonwhite race, higher systolic blood pressure, glomerular filtration rate <60, and higher hemoglobin A1C were independent predictors of serum NfL in this cohort but diastolic blood pressure, durations of hypertension or diabetes mellitus, and lipid levels were not. In total, cardiovascular disease risk factors explained 19.2% of the variability in baseline NfL levels. Conclusions—: Serum NfL levels predict incident stroke and add considerably to the discriminatory power of the Framingham Stroke Risk Score in a cohort of middle-aged and older adults with diabetes mellitus.